Politics and trade in Britain, 1776-1914.
1 online resource (l, 272 pages)
Keywords: This volume takes up the story of exacerbated political divisions from 1841 onwards, with a clearer demarcation in political life caused at least partly by commercial policy considerations. Ultimately, the success of free trade policies, implemented by Sir Robert Peel after 1841, saw the reconfiguration of political parties and had lasting effects and impact on party politics. Yet in the period up to 1879, there was a broad consensus on maintaining the free trade settlement of 1846. This period, often seen as a ⁰́₈free trade interlude⁰́₉ book-ended by a far more complex range of opinions, policies, and strategies surrounding commercial policy, was characterised by British manufacturing expansion, deeper penetration of foreign and colonial markets, and the adoption of freer trade policies by foreign nations. Ultimately, none of these developments lasted in the long term. By the end of 1879, commercial policy was again controversial. The type of sources in this volume includecorrespondence from The Panmure Papers, the Later Correspondence of Lord John Russell, and diary material from Lord Ashley and John Bright. There is also a considerable body of material from newspapers, including the Morning Chronicle, Northern Star, Manchester Guardian, and Liverpool Mercury. Manuscript materials from Richard Cobden, John Benjamin Smith, and Lord John Russell among others are also present.